تصميم ألعاب لغوية لتعليم اللغة العربية من خلال الكلمات الإندونيسية ذات أصل قرآني - Yusri sofa mubarok; Hadil ismail (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
This study aims to provide the teacher and learner knowledge of the Arabic language to speakers of other languages ​​through one of the teaching methods, which are language games from Indonesian words of Quranic origin from Surat Al-Fatihah to Surat Al-Nisaa, To achieve this goal, the researcher used in his research the descriptive analytical approach that paved the way for the researcher to analyze the Indonesian vocabulary of Qur'anic origin , The study produced a number of results, the most important of which is the presence of Indonesian words of Qur'anic origin from the Qur’an translated into the Indonesian language (al-quran dan terjemahanya) from Surat Al-Fatihah to Surat Al-Nisaa and reached 102 and each language skill have one game.